The Baby Sleep Quality Using of White Noise in Hypno Sleeping Process - Meilicha Anggraini Pratiwi; Ira Kusuawaty; Desy Setiawati (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
Background: Sleep is an important activity for humans. Especially babies, because one of the factors that affect the growth and development of babies is sleep. Methods to overcome poor sleep quality that are fast and effective are still lacking for infants under 6 months of age. There is one effective method is to use white noise in the hypno sleeping process in infants aged 0-6 months. Purpose: This study aims to determine the effectiveness of using white noise in the hypno sleeping process in infants aged 0-6 months. Methods: This research belongs to the type of quantitative research with a Pre Experiment research design in the form of One Group Pretest Posttest Design. Sampling using purposive sampling method and added a correction of 10%. The sample of this study were infants aged 0-6 months in PMB Rabiah Palembang City who had poor sleep quality and who met the inclusion criteria were 33 infants. Results: The results of the study using Mc Nemar statistical test and obtained a significant value value = 0.000 (ρ value <0.05) meaning that the use of white noise is effective in the hypno sleeping process in infants aged 0-6 months. Conclusion: The use of white white noise is effective in the hypno sleeping process in infants aged 0-6 months.